A review on the integrative approach for economic valuation of forest ecosystem services - Raihan, Asif (Journal of Environmental Science and Economics, 2023)
Forests have the most biodiversity and provide vital ecosystem services. They offer numerous forest-related services, some of which can be commercialized. This improves social, cultural, health, and scientific life. Nonmarketable and intangible services are discounted because people think they're endless and free. Humans have changed the natural and social worlds through using resources and improving well-being. Public and private decision-makers often compete over natural capital. The loss of biodiversity, climate change, and global warming are interconnected with social development and ensuring an acceptable level of well-being for the majority of humanity, making it difficult for a single, individual approach to estimating the value of these goods and services to generate and support decisions and policies in these complex areas. The complexity of ecosystem products and services requires an integrated assessment with cutting-edge technologies and approaches using a pluralist framework of heterogeneous values. This evaluation should encompass costs and benefits of several ecosystem commodity and service applications. These usage' effects on economic, social, and cultural advancement are also crucial. The extensive and thorough enthronization of natural ecosystems can affect the amount and quality of ecosystem goods and services; thus, it is vital to quantify the complicated inverse effect from civilization to nature. Studies show that incorporating sustainability sciences approaches into an integrative assessment approach may be vital to environmental policy in the future.